2013
DOI: 10.1177/1078155213502103
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of multiday palonosetron with aprepitant and low-dose dexamethasone in prevention of nausea and emesis among patients with multiple myeloma and lymphoma undergoing autologous hematopoietic stem cell transplant: A pilot study

Abstract: This triplet regimen was feasible with acceptable safety profile in the autologous hematopoietic stem cell transplant setting. Emetic control was best achieved in the acute phase. Lesser degree of emetic and nausea control in the delayed and extended phases impacted quality of life. Our results warrant further evaluation in a larger autologous hematopoietic stem cell transplant population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Four detailed articles [11][12][13][14] evaluating the acute emetogenicity of HDMel in patients undergoing CINV prophylaxis with different schedules reported a low emesis incidence (0-41%). Other research on HDMel reported delayed vomiting as moderately frequent (12-66%), despite adequate prophylaxis [11,[13][14][15][16]. Finally, our analysis of the literature showed a similar rate of CINV in the two melphalan schedules (MEL200×1 and MEL100×2).…”
Section: Melphalan Emetogenicity During Transplantssupporting
confidence: 71%
See 4 more Smart Citations
“…Four detailed articles [11][12][13][14] evaluating the acute emetogenicity of HDMel in patients undergoing CINV prophylaxis with different schedules reported a low emesis incidence (0-41%). Other research on HDMel reported delayed vomiting as moderately frequent (12-66%), despite adequate prophylaxis [11,[13][14][15][16]. Finally, our analysis of the literature showed a similar rate of CINV in the two melphalan schedules (MEL200×1 and MEL100×2).…”
Section: Melphalan Emetogenicity During Transplantssupporting
confidence: 71%
“…Eleven papers, reporting results of clinical trials, that explored the effectiveness of a certain prophylaxis for CINV in patients undergoing HDMel conditioning for autologous SCT are included (Table 1). Of these 11 studies, 2 are randomized, comparative, and prospective [7,18], 6 are single-arm prospective [7,12,15,16,18,20], 2 are comparative and retrospective [10,19], and 1 is single-arm retrospective [13] ( Table 1). From these experiments, only aprepitant, fosaprepitant, and olanzapine were compared to standard therapy in the setting of HDMel.…”
Section: Efficacy Of Combination Antiemetic Therapymentioning
confidence: 99%
See 3 more Smart Citations